Productivity of Several Soybean Varieties (Glycine Max L.) Based on Pruning of Corn (Zea Mays L.) Leaves - Fahmi, Zul; Syarif, Auzar; Dwipa, Indra (Universitas Labuhanbatu, 2023)
This research on intercropping productivity of several soybean varieties based on pruning corn plant leaves was carried out on road Alai Kapalo Koto, Limau Manis, Pauh District, Padang at an altitude of 101 meters above sea level from July to November 2022. The purpose of this research is to investigate the relationship between various soybean types and pruning. The best corn leaf for plant development and production, as well as intercropping productivity. This study used a factorial completely randomized design (CRD) with three replications. The first component was soybean cultivars, which had four treatment levels (Anjasmoro, Grobogan, Devon 1, and Dega 1), and the second factor was the quantity of corn leaf pruning, which had four treatment levels (Pruning 0 1/2, 1/3, and 1/4 Corn Plant Leaves). The number of clipped leaves is determined from the base of the stem. The findings revealed that there was no interaction between the quantity of leaf pruning applied to maize plants and select soybean varieties and plant development and yield in an intercropping system. trimming half of the leaves of a maize plant has a greater influence on NKL and ATER values than other trimming levels. When compared to other soybean varieties, the Anjasmoro soybean variety produced higher ATER soybean yields. According to the findings of this study, 1/2 leaf pruning of corn plants and the Anjasmoro type of soybean plants should be used in an intercropping system